Nano filtration membrane separation prediction system for analysis of ion transport mechanisms / Norhaslina Mohd Sidek - Mohd Sidek, Norhaslina (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The previous studies on Nano filtration (NF) modeling more focused on the work to update the existing predictive models to enhance its applications. There is still lack of research which successfully creates a user friendly prediction system for analysis of ion transport mechanisms. In this study, a MATLAB based NF prediction system (NF-BIN) utilizing Donnan Steric Pore (DSP) model was developed. Locally fabricated polysulfone (PSF) membranes with three different polymer concentrations; 19%, 21% and 23% were characterized in terms of pore radius, rp ratio of membrane thickness to porosity, Ax/Ak and effective charge density, Xd using uncharged and charged solutes rejection data.The rejection prediction performance was then performed to predict the significant of ion transport mechanisms of two factors: Donnan and steric and three modes: diffusion, electro migration and convection. The results obtained indicated that NF-BIN has a good potential as an ideal predictor of NF membrane separation behavior for high technology filtration industry.